Decomposing scale, technique and composition effects of foreign direct investment on environmental quality - Chen, Kong San; Chin, Lee; Law, Siong Hook; Kaliappan, Shivee Ranjanee; Foo, Yong Seong (Springer, 2024)
This study aimed to investigate how the decomposing scale effect, technique effect and composition effect of foreign direct investment (FDI) impact on carbon dioxide (CO2) emissions for 115 nations spanning 1999 to 2019 by employing Generalised Method of Moments (GMM) model. The results indicated that FDI, real GDP per capita, capital-labor ratio, institutional quality and urbanization increase CO2 emissions while the square of real GDP per capita and trade openness contributed to reducing CO2 emissions. Also, our findings fail to support Environmental Kuznets Curve (EKC) theory. The outcomes of this research illustrated that scale effect dominates composition effect and followed by technique effect. The interaction effect of FDI and technique effect has the least influence on CO2 levels in reducing the harmful effects of FDI on CO2. Furthermore, it should be highlighted that although FDI increases CO2 emissions, its detrimental impact on CO2 emissions is moderately mitigated by its interactions with three economic mechanisms. Therefore, it is necessary to enhance the technical processes of production as well as the development of modern technologies. We recommended that policymakers balance sustainable economic development with environmental sustainability by considering the indirect effects of factors on CO2 emissions.